2012
DOI: 10.1371/journal.pone.0046301
|View full text |Cite
|
Sign up to set email alerts
|

H(2)S-Releasing Aspirin Protects against Aspirin-Induced Gastric Injury via Reducing Oxidative Stress

Abstract: The aim of this study was to examine the effect of ACS14, a hydrogen sulfide (H2S)-releasing derivative of aspirin (Asp), on Asp-induced gastric injury. Gastric hemorrhagic lesions were induced by intragastric administration of Asp (200 mg/kg, suspended in 0.5% carboxymethyl cellulose solutions) in a volume of 1 ml/100 g body weight. ACS14 (1, 5 or 10 mg/kg) was given 30 min before the Asp administration. The total area of gastric erosions, H2S concentration and oxidative stress in gastric tissues were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 63 publications
(64 reference statements)
0
35
0
2
Order By: Relevance
“…Intraperitoneal administration of 2-acetyloxybenzoic acid 4-(3-thioxo-3H-1, 2 dithiol-5-yl) phenyl ester (ACS14, Saspirin), a form of aspirin that releases H2S, prevented aspirin-induced gastric ulceration; this protective effect of Saspirin was reproduced by NaHS establishing that H2S was responsible for the ameliorative effect (54). The mechanism of H2S amelioration of aspirin-induced injury involved a decrease in the markers of oxidative stress and a reversal of aspirin-induced increased expression of xanthine oxidase in the gastric mucosa (54).…”
Section: Renal Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Intraperitoneal administration of 2-acetyloxybenzoic acid 4-(3-thioxo-3H-1, 2 dithiol-5-yl) phenyl ester (ACS14, Saspirin), a form of aspirin that releases H2S, prevented aspirin-induced gastric ulceration; this protective effect of Saspirin was reproduced by NaHS establishing that H2S was responsible for the ameliorative effect (54). The mechanism of H2S amelioration of aspirin-induced injury involved a decrease in the markers of oxidative stress and a reversal of aspirin-induced increased expression of xanthine oxidase in the gastric mucosa (54).…”
Section: Renal Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Similarly, H 2 Sindomethacin (61), H 2 S-mesalamine (64), and H 2 S-naproxen (63) were also shown to cause significantly less damage to the stomach compared with their respective parent compound. In a recent study, H 2 S-donating ASA (ACS14) was shown to spare the stomach of rats from the harmful side effects of ASA when given 30 min before ASA administration (41). ACS14 also abrogated ASA-induced up-regulation of COX-2 expression, but it had no effect on the reduced PGE 2 levels; it also attenuated ASA-suppressed superoxide dismutase-1 expression and glutathione (GSH) activity (41).…”
Section: H 2 S-donating Nsaids Do Not Cause Stomach Ulcersmentioning
confidence: 99%
“…In a recent study, H 2 S-donating ASA (ACS14) was shown to spare the stomach of rats from the harmful side effects of ASA when given 30 min before ASA administration (41). ACS14 also abrogated ASA-induced up-regulation of COX-2 expression, but it had no effect on the reduced PGE 2 levels; it also attenuated ASA-suppressed superoxide dismutase-1 expression and glutathione (GSH) activity (41). These data suggest that ACS14 enhances mucosal integrity by inhibiting oxidative stress in the gastric tissue.…”
Section: H 2 S-donating Nsaids Do Not Cause Stomach Ulcersmentioning
confidence: 99%
“…Derivatives of naproxen, diclofenac, and indomethacin which can release H2S have been reported [125128]. Phosphatidylcholine-associated NSAIDs as well as NO- and H2S-releasing NSAIDs are under extensive preclinical testing for their influence on NSAID induced GI toxicity [129, 130].…”
Section: Recent Advances In Nsaid Treatmentsmentioning
confidence: 99%